Michelle Swanson project based learning and technology - Arnold, Craig (California : Canter & Associates, 1997)
In this video, presenter introduces the steps for effective project-based learning and also illustrate effective ways to construct project relevant to students' lives and integrate technology and content to better prepare students to contribute to society
Video is accompanied by 1 leader's manual
Executive producer, Kathy Winberry ; writer, Teresa Langness
Host: Hall Davidson
Presenter: Michelle Swanson
Keywords: Educational technology; High technology and education